Sanokondu: The birth of a multinational network for the development of healthcare leadership education. Issue 2 (19th April 2018) - Busari, Jamiu; Chan, Ming-Ka; Dath, Deepak; Matlow, Anne; Meschino, Diane de Camps
Abstract : Purpose: This paper aims to describe the evolution of Sanokondu, highlighting the rationale, achievements and lessons learnt from this initiative. Sanokondu is a multinational community of practice dedicated to fostering health-care leadership education worldwide. This platform for health-care leadership education was conceived in 2014 at the first Toronto International Summit on Leadership Education for Physicians (TISLEP) and evolved into a formal network of collaborators in 2016. Design/methodology/approach: This paper is a case study of a multinational collaboration of health-care leaders, educators, learners and other stakeholders. It describes Sanokondu 's development and contribution to global health-care leadership education. One of the major strategies has been establishing partnerships with other educational organizations involved in clinical leadership and health systems improvement. Findings: A major flagship of Sanokondu has been its annual TISLEP meetings, which brings various health-care leaders, educators, learners and patients together. The meetings provide opportunities for dialog and knowledge exchange on leadership education. The work of Sanokondu has resulted in an open access knowledge bank for health-care leadership education, which in addition to the individual expertise of its members, is readily available for consultation. Sanokondu continues to contribute to scholarship in health-care leadership through ongoing research, education and dissemination in the scholarly literature. Originality/value: Sanokondu embodies the achievements of a multinational collaboration of health-care stakeholders invested in leadership education. The interactions culminating from this platform have resulted in new insights, innovative ideas and best practices on health-care leadership education.